DEVELOPMENT AND EFFICIENCY EVALUATION OF CARGO TRANSPORTATION TECHNOLOGY IN HIGH-CAPACITY CONTAINERS WITH LOAD LIFTING VERTICAL STAYS IN ROADRAIL NETWORK - I. M. Ryabov; V. Gorina (Вестник СибАДИ)
Introduction. At present the transportation of current high-capacity containers in road-rail mixed network is carried out only by means of the specialized sites with the equipment for their reloading. The number of such sites on the railway transport network in the Russian Federation is significantly fewer than the number of conventional cargo railway stations without such equipment, which leads to distance, time and cost of delivery increasing, the efficiency of the road transport use reducing due to a large downtime. The transportation of high-capacity containers by road rolling stock (RS) is often carried out over the considerable distances in the reverse direction by rail. In order to eliminate these shortcomings, the authors of the article formulated the purpose of the work – the development and evaluation of the efficiency of the technology of goods transportation in high-capacity containers with load lifting stays in a road-railway network based on a transportation case study. Within the framework of which a new design of a container with load lifting stays has been developed which allow to carry out loading and unloading operations with the container at conventional cargo railway stations without the use of specialized equipment of container terminals, as well as the efficiency evaluation of the technology of the containers transportation in road-rail network based on a case study.Materials and methods. The study uses the following methods of theories: cars operation, car operational properties, transport processes; analytical and numerical methods.Results. It has been determined that the cargo delivery time according to the new technology of transportation of high-capacity containers with load lifting stays from the Volga brewery to Novosibirsk has decreased by 24.6%, the time of operation of road RS has decreased by 10 times, and the annual economic efficiency of the new technology application is 1.55 million rubles in comparison with the current technology.Discussion and conclusions. Based on the case study of the use of a new technology for the transportation of high-capacity containers with load lifting stays in a mixed network it has been found that this technology allows: A) to reduce the number of delivery operations by 24%; B) to reduce the delivery time by 24.6% and the operation time of motor transport by 10 times. C) to obtain the annual economic effect of the application of the new technology in the amount of 1.55 million rubles.